Determination of the P-T conditions and depths of magma storage zones for two distinct quaternary lava flows in the Southeast of Mount Ağrı (Eastern Anatolia, Turkey) - Gullu Deniz Dogan-Kulahci (PLoS ONE, 2025)
This study aims to determine the pressure (P)-temperature (T) conditions and depths of magma storage zones for two distinct lava flows located to the southeast of Mount Ağrı (5137 m), the highest stratovolcano in Turkey. The mineralogical–petrographic observations, whole-rock-trace and mineral chemistry, and geochronological (⁴⁰Ar/³⁹Ar dating) features of these lava flows were examined to provide the petrologic and temporal evolution of volcanic activity in the region. The flow referred to as Phase 1, with SiO₂ content ranging from 49.2% to 51.2%, was classified as trachybasalt, while the flow identified as Phase 2, with SiO₂ content between 62.42% and 63.4%, was classified as andesite. The whole-rock 40 Ar/ 39 Ar ages of samples from Phase 1 and Phase 2 were determined to be 57.70 ± 21.44 ka and 19.09 ± 5.59 ka, respectively. The older and more mafic Phase 1 flow displays a mineral assemblage of plagioclase + olivine ± oxide macrocrysts, microphenocrysts, and microlites. Conversely, the younger and more differentiated Phase 2 flow comprises a mineral assemblage of plagioclase + orthopyroxene ± clinopyroxene ± oxide macrocrysts, microphenocrysts, and microlites. Phase 1 is phaneritic with a scoriaceous texture and contains labradorite–composition plagioclase and Fo-rich olivine, whereas Phase 2 is aphanitic with a glassy texture, characterized by andesine–labradorite plagioclase, enstatite, and augite. EPMA analysis results and P-T calculations derived from equilibrated macrocrysts and microphenocrysts show that, assuming an average crustal density of 2.70 g/cm³, Phase 1 was emplaced at a depth of 38 km, with crystallization temperatures of 1186 °C from plagioclase data and approximately 1200 °C from olivine. In Phase 2, temperatures derived from plagioclase, clinopyroxene, and orthopyroxene are ~ 1128; 1147 and 1061 °C, with corresponding pressures of 8, 6, and 5 kbar, yielding calculated depths of 30 km, 23 km, and 19 km, respectively. These findings demonstrate that Phase 1 exhibits higher crystallization temperature, pressure, and depth values than Phase 2. Overall, the results reveal two distinct magma storage zones southeast of Mount Ağrı, active at different times during the Quaternary, which produced both mafic and intermediate volcanic products, with one located at a shallower and the other at a deeper level.